Synergistic effects of seed inoculation with Azospirillum brasilense and nitrogen sources on double cropped maize production in tropical savanna of Brazil - Kaneko, Flávio Hiroshi; Sabundjian, Michelle Traete [UNESP]; Ferreira, João Paulo [UNESP]; Gitti, Douglas de Castilho; Nascimento, Vagner [UNESP]; Leal, Aguinaldo José Freitas; Buzetti, Salatiér [UNESP]; dos Reis, André Rodrigues [UNESP]; Arf, Orivaldo [UNESP] (Southern Cross Publishing, 2016)
Nitrogen (N) fertilization on maize crops has been going through modifications due to the use of technologies such as biological N fixation and modified fertilizers. This study aimed to evaluate the effect of seed inoculation with Azospirillum brasilense (with and without inoculation), N sources (urea and polymer coated urea) and side-dressed N levels (0; 45; 90; 135 and 180 kg ha-1), on double cropped maize in two regions of Brazilian savanna (Chapadão do Sul and Selvíria, State of Mato Grosso do Sul). The experiment design was arranged in randomized plots at a 2 x 2 x 5 factorial scheme with 4 replications. The following characteristics were evaluated: plant population (plants ha-1), plant dry matter, leaf N concentration, stem diameter, weight of 100 grains and grain yield. Seed inoculation with A. brasilense did not increase double cropped maize yield in both environments. The application of coated urea provided higher dry biomass, however, the polymer coated urea application showed no effect on grain yield in comparison to conventional urea. Increasing side-dressed N levels is the main key factor responsible to improve the double cropped maize yield in tropical Brazilian savanna.
Keywords: Biological N fixation; Coated fertilizers; Nitrogen fertilization; Polymers; Zea mays